SPEECH ACTS IN THE POEM "AKU" BY CHAIRIL ANWAR: A PRAGMATICS ANALYSIS - Rutmintauli Simanjuntak (ELLITE ( Journal of Education, Linguistics, Literature and Language Teaching), 2024)
This study analyzes the speech acts in the poem "Aku" by Chairil Anwar using a pragmatic approach to uncover the meaning contained in locutionary, illocutionary, and perlocutionary acts. As one of the most iconic poems in Indonesia, "Aku" embodies expressions of freedom, resistance, and individual existence articulated through distinctive language choices. The aim of this study is to understand how the message in this poem is communicated through these three types of speech acts and its relevance in the social and cultural context of Chairil Anwar's era. This research uses a qualitative method with descriptive analysis. The data, in the form of the poem "Aku", is analyzed based on speech act theory. The analysis process includes identifying the types of speech acts, interpreting the meaning based on the pragmatic context, and evaluating the perlocutionary effects generated by each line of the poem. The results show that the poem is rich in locutionary acts that affirm the poet's self-expression, illocutionary acts that reflect a stance of resistance to social norms, and perlocutionary acts that inspire readers to reflect on the meaning of freedom and courage. The conclusion of this study emphasizes that the poem "Aku" by Chairil Anwar is not only an aesthetic literary work but also imbued with pragmatic values that reinforce the message of courage, freedom, and personal identity. These findings are expected to enrich pragmatic studies in Indonesian poetry and provide new insights into how speech acts can be used to understand the messages in literary works.